MANAJEMEN PENGAJARAN DI STUDIO DISAIN ARSITEKTUR - Liliany Sigit Arifin; Istiawati Kiswandono (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2002)
Design activities in a studio do not only involve students, but also need to be accompanied by tutors, guest lecturers, consumers, and the professionals. Each of these individuals gives different contribution according to each own competency. The involvement that takes place between these individuals does not only consist of tutorials, and is not just an activity in which